Visualizing orthogonal RNAs simultaneously in live mammalian cells by fluorescence lifetime imaging microscopy (FLIM) - Nadia Sarfraz; Emilia Moscoso; Therese Oertel; Harrison J. Lee; Suman Ranjit; Esther Braselmann (Nature Communications, 2023)
No multi-color RNA fluorescent tags are currently available for use in live cells. Here, the authors show that fluorescence lifetime imaging microscopy is advantageous for multiplexed RNA visualization while achieving robust cellular contrast.